Evaluasi Kesesuaian dan Proyeksi Pengembangan Bengkel Praktik Teknik Sepeda Motor Berbasis Standar Industri - Ciesa Fama Febrikadiyani; Valiant Lukad Perdana Sutrisno (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to determine the relevance of the Motorcycle Engineering Workshop standards at the Department of Mechanical Engineering Education, UNS, to current industrial standards and to formulate a development projection to better align the workshop with the standards of the automotive industry. This study employed a mixed methods approach using a sequential explanatory design, in which quantitative data were collected first, followed by qualitative data. The quantitative data were obtained using a total sampling technique, while the qualitative data were collected through purposive sampling. Data collection techniques included observation and interviews. Quantitative data were analyzed descriptively using percentage calculations, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The result showed that the Occupational Health and Safety (OHS) aspect achieved a percentage of 85.7%, categorized as "highly appropriate"; the workshop functional space aspect obtained 40.0%, categorized as "moderately appropriate"; and the practical equipment suitability aspect reached 46.4%, also categorized as "moderately appropriate." Overall, the relevance of the Motorcycle Engineering Workshop standards to industrial standards reached 51.87%, which falls into the "moderately appropriate" category. The proposed development projection focuses on redesigning the workshop layout, improving facilities and practical equipment, strengthening the workshop management system, and optimizing the implementation of Occupational Health and Safety (OHS) to better meet the needs of the business and industrial sectors.